701 Infections disease among professional divers: review of literature 2016. (24th April 2018) - Pougnet, R; Pougnet, L; Alliot, I; Lucas, D; Loddé, B; Dewitte, JD
Abstract : Introduction: The occupational divers are subject to numerous risks. For instance, divers can get infections. We review the infectious diseases in professional divers. Materials and methods: This is a literature review until 30/05/2017. The research was conducted on Medline and Scopus databases, in French and English languages. Results: Fifteen papers report cases of infections in professional divers. These are mainly skin infections, but also ENT and ophthalmological infections. Discussion-conclusion: According to data collected, infections among professional divers are quite rare. These diseases are not specific to the workplace, and are comparable with data on recreational diving. Prevention is mainly based on hygiene and equipment maintenance.